IMPLEMENTASI APLIKASI SISTEM PAKAR MENGGUNAKAN METODE FORWARD CHAINING - Alwendi Alwendi; Andi Saputa Mandopa (FAKULTAS TEKNIK, 2023)
The Expert System is a solution that helps parents diagnose possible hyperactivity in their children from an early age. This expert system is designed for several stages including system requirements analysis, design, coding and testing. This expert system is represented in the form of rules and its reasoning method is forward chaining, namely H. concludes hyperactivity from several symptoms. The result of the system is a kind of hyperactivity from diagnosis and solution to diagnosis. In operation, this system has two user rights, namely expert users and ordinary users. Experts in this system are child development experts. This system can process disease information, symptoms and context. The result of this system is the result of a diagnosis of hyperactivity based on the presence of symptoms. Hyperactivity Disorder is a pattern of behavior in someone who doesn't want to relax. Hyperactive children are children with attention deficit disorder. Hyperactivity or Attention Deficit Hyperactivity Disorder (ADHD) or also known as Hyperkinetic Disorder. Hyperactivity is a combination of attention problems, hyperactivity and impulsive behavior. The diagnosis of hyperactivity is usually made by a doctor or child development specialist. In fact, parents can also diagnose early the possibility of hyperactivity in children by observing their child's behavior in everyday life, especially through the way they communicate and interact socially. with peers and children's imagination.